テリパラチド投与によるSAPHO症候群の慢性硬化性下顎骨骨髄炎の治療経験 - 上田, 愛; 宮崎, 晃亘; 大西, みちよ; 島西, 真琴; 平塚, 博義; 小林, 淳一 (日本口腔外科学会雑誌, 2016)
Synovitis-acne-pustulosis-hyperostosis-osteitis (SAPHO) syndrome is characterized by sterile osteomyelitis and pustular skin disease. Little is known about its pathogenesis, and no effective treatment methods have been established to date. We report the case of 69-year-old man with chronic sclerosing osteomyelitis of the mandible associated with SAPHO syndrome. After a previous surgical treatment, the patient’s lesion was resistant to antibiotics and hyperbaric oxygen therapy; therefore, teriparatide was administered. After 7 months of teriparatide treatment, the patient’s spontaneous pain disappeared, and computed tomographic and magnetic resonance imaging scans showed improvements in the bone structure and quality of the mandible. These findings suggest that suppression of bone remodeling occurs in SAPHO syndrome, similar to BRONJ.